Effect of increasing GleptoForte dosage in newborn pigs on sow and litter performance - Regehr, Meghan; Williams, Hayden E.; Jones, Cassandra K.; DeRouchey, Joel M.; Tokach, Michael D.; Woodworth, Jason C.; Goodband, Robert D.; Dritz, Steven S.; Holtcamp, A. (My University, 2017)
Newborn pigs are extremely susceptible to iron deficiency because they are not born with adequate iron stores. Symptoms of iron deficiency include poor circulation, lethargy, and eventually death. In an effort to prevent iron deficiency, GleptoForte was developed as an injectable iron in the form of Gleptoferron. The purpose of this study was to test differing dosages of Gleptoforte on preventing anemia, and evaluate the effects on newborn pigs, sow, and litter performance. This 21 day farrowing study consisted of 336 newborn pigs. This amounted to a total of 28 litters being utilized. Approximately 3 day after birth, all piglets were weighed and organized into a completely random design of 56 pigs per treatment. A total of 6 treatments were used, with the negative control being no iron injection. Of the Gleptoforte, 50, 100, 150, 200, or 200mg plus a 100mg booster at day 11 of farrowing were given. The criteria tested were as follows: ADG, Hemoglobin, Hematocrit, Serum Fe, and Total Iron Binding Capacity. A lack of iron injection – the negative control - resulted in the poorest growth response. The greatest growth response was a result of the 100mg Gelptoforte injection. Adding a 100mg booster to the 200mg iron injection improved the blood criteria. However, the addition of a booster did not affect the growth response compared to the 200mg treatment without a booster, therefore suggesting that the 100mg booster made no significant difference.
Keywords: Fall 2017